Integrated public lands management : principles and applications to national forests, parks, wildlife refuges, and BLM lands - Loomis, John B. (Columbia University Press, 2002)
Integrated Public Lands Management is the only book that deals with the management procedures of all the primary public land management agencies National Forests, Parks, Wildlife Refuges, and the Bureau of Land Managementin one volume. This book fills the need for a unified treatment of the analytical procedures used by federal land management agencies in planning and managing their diverse lands. The second edition charts the progress these agencies have made toward the management of their lands as ecosystems. It includes new U.S. Forest Service regulations, expanded coverage of Geographic I.